The Use of Code-Mixing in Denny Sumargo and Fiki Naki's Podcast - Karina; Mardiah; Suparni (Yayasan Nurul Iman Muara Gading Mas, 2025)
This study aims to identify the forms of code-mixing in the Denny Sumargo and Fiki Naki video podcast. This research employed a qualitative descriptive method. The data were sourced from a video podcast episode titled “Playboy internasional? Bucin Serius Mau Nikah Muda Sama Tugba!! (Fiki Naki)”. Data collection utilized observational and note-taking techniques. Furthermore, the data analysis was conducted through six stages: unitizing, sampling, recording, reducing, inferring, and narrating. The results revealed 91 utterances containing code-mixing within the podcast. Specifically, these consisted of 40 code-mixings in the form of words, 27 in the form of phrases, and 24 in the form of clauses.